1986
DOI: 10.1139/b86-060
|View full text |Cite
|
Sign up to set email alerts
|

Salt marshes of Atlantic Canada: their ecology and distribution

Abstract: This paper reviews the status of research on the Atlantic salt marshes of eastern Canada. The floristics, habitats, and biophysical aspects of the Atlantic salt marshes are described and aspects relating to anthropogenic influences on the Atlantic marshes are discussed in the context of contemporary rural settlement and vulnerability to offshore oil development. Guidelines for environment management, protection, and rehabilitation research are proposed. Such guidelines are deemed important since more than half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…The Labrador salt marshes are grazed by migratory waterfowl and are important feeding, mating and staging areas for some 75 migratory bird species, even though their total area is probably <200 km 2 . Birds and ice scouring are factors in the salt marsh structure in Panne and Sward communities, as well as intertidal mud flats and shorelines (Roberts and Robertson 1986;Adam 1993).…”
Section: Salt Marshesmentioning
confidence: 99%
“…The Labrador salt marshes are grazed by migratory waterfowl and are important feeding, mating and staging areas for some 75 migratory bird species, even though their total area is probably <200 km 2 . Birds and ice scouring are factors in the salt marsh structure in Panne and Sward communities, as well as intertidal mud flats and shorelines (Roberts and Robertson 1986;Adam 1993).…”
Section: Salt Marshesmentioning
confidence: 99%
“…21). In x Du- (Dutilly et al 1954(Dutilly et al , 1958Dignard et al 1991) to Labrador (Roberts & Robertson 1986), D. fisheri ssp. psilosantha is known to occur in the wettest parts of salt marshes and brackish to gravelly shores.…”
Section: Methodsmentioning
confidence: 99%
“…Depressions may also be man-made (where mud is taken to build decoys for goose hunting) (Dionne 1976(Dionne , 1978 or result from trampling and feeding (on rhizomes) by geese (Jefferies et al 1979). Feeding activities of large numbers of geese at pool margins increase pool size through abrasion and digging creates small depressions that may evolve to larger pools (Roberts & Robertson 1986). …”
Section: Ice Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otte et al (2004) suggested that it acts as an herbivore deterrent, as Morris et al (2002) showed that S. alterniflora fertilized with nitrogen, and therefore containing lower levels of DMSP (Otte and Morris, 1994;Mulholland and Otte, 2000) were consumed more by rice rats than plants located in unfertilized areas. Those authors also suggested that DMSP may act as a cryoprotectant in S. alterniflora, as its geographical distribution ranges from the U.S. warm southeastern salt marshes to the eastern Canadian coast of Labrador, where temperatures in the winter are below freezing (Hitchcock, 1971;Roberts and Robertson, 1986).…”
Section: Introductionmentioning
confidence: 99%